The impact of education on subjective well-being: a meta-analysis based on 59 empirical studies - Xuemin Dong; Zhe Xing; Haixin Song; Dexin Hu (Frontiers in Psychology)
IntroductionSubjective well-being (SWB) has emerged as a prominent research focus, especially in the context of specific dimensions of education (educational level, higher education participation, and lifelong learning engagement). This study aimed to assess whether education (educational level, higher education participation, lifelong learning engagement) influences SWB, and to explore whether moderators such as rural -urban residence and publication year alter this relationship.MethodsFollowing the PRISMA guidelines, we conducted a systematic review and meta-analysis. After applying rigorous eligibility criteria (e.g., empirical studies reporting relationships between education and SWB, specific published years from 2012 to 2023 and languages including English and Chinese), this study screened 59 empirical studies and extracted 185 effect sizes that could be used in the meta-analysis. First, we examined the relationship between education and SWB and further analyzed the moderators to explore the effects of rural -urban factors and publication year.Results(1) Educational level and higher education participation significantly influenced SWB, while lifelong learning engagement showed a weaker but significant positive association, partially supporting our initial hypothesis. (2) The relationship between education and SWB was moderated by rural -urban factors. (3) Publication year within the studied time also exerted a significant moderating effect.DiscussionThis study clarified that education should be emphasized continuously, and education equity ought to be improved further so that both rural and urban residents gain high levels of SWB in the future. These results of the paper will provide insights into how SWB interacts with education and offer useful suggestions of improving SWB from an educational perspective.